PENGOLAHAN LIMBAH POLIPROPILEN MENJADI BAHAN BAKAR CAIR MELALUI METODE PIROLISIS - Bemis, Restina; Jamarun, Novesar; Arief, Syukri (Jurnal Riset Kimia, 2012)
Plastics become the biggest environmental problem when it accumulate in landfills because its non-biodegradable properties. To handle the problems, the plastics were processed to produce liquid fuels by means pyrolysis method which was in this case with and without a catalyst. In this work, polypropylene was used as a precursor and SiO2, zeolites, CaO, Fe as catalysts. FTIR spectrum of pyrolized polypropylene with and without catalysts both have shown C = C functional group at 1648 cm-1. GCMS analysis confirmed the availability of chain length of hydrocarbon between C7 -C27 which is mixture of kerosene and diesel fractions. Catalysts can lower the temperature and time reaction of pyrolysis process as they increase rendement (%) of product. Liquid fuels that produced from polypropylene pyrolysis without catalyst was 72.06%, and with catalysts were 79.59% (SiO2), 74.76%, (zeolite), 76.80% (CaO), and 76.83% (Fe).